Surgeons' fear of getting infected by COVID19: A global survey - An Y; Bellato V; Konishi T; Pellino G; Sensi B; Siragusa L; Franceschilli M; Sica GS; S-COVID Collaborative Group; Pejkova S (John Wiley & Sons Ltd, 2020)
During the last three months, COVID-19 pandemic had led to a serious backlog of operations globally, and plans for restarting operation are imperative1–3. Recommendations for surgical activities were studied, aiming to protect the surgical staff from being infected4,5. In the meantime, it is also important to give attention to the surgeon's personal feeling during work. We conducted a survey to investigate global surgical practices during the COVID-19 pandemic6, and the surgeon's personal feeling was also investigated in the survey. In this special letter, we performed multivariate analysis to explore factors that associated with surgeon's fear of getting infected by COVID-19. In total, 1124 surgeons from 936 centers in 71 countries replied to the questions. Regarding surgeon's satisfaction towards hospital's preventive measures, 612 of the respondents (54·4%) agreed that their centers were taking enough preventive measures to avoid in-hospital transmission. With respect to the results by nations, respondents from the UK reported lowest satisfaction (6/27, 22·2%), while those from China (70/73, 95·9%) and the Netherland (26/33, 78·8%) reported higher satisfaction. When asked about the personal fear of getting sick or infecting others (1 point = never, 5 points = always), the respondents in overall reported a relatively high score (the mean ± SD of all respondents: 3·7 ± 1·3). The respondents from Mexico (4·7 ± 0·6, n = 31), the US (4·2 ± 1·2, n = 51) and Turkey (4·2 ± 1·0, n = 38) had higher scores, while those from the Netherlands (2·5 ± 1·2, n = 33) and China (2·6 ± 1·4, n = 73) had lower scores. In order to explore factors that were associated with surgeon's fear of getting infected, univariate and multivariate analysis were performed using the data from the entire survey (including content about COVID-19 testing policies, protective measures and COVID-19 caseload) (Table 1). Surgeons with personal fear were defined as those with 4 or 5 points in the question “Have you ever been afraid of getting sick or infecting others because of your work?”. The factors with P values < 0·1 in the univariate analysis were high risk country (P = 0·067), shortage of gloves (P = 0·077), shortage of gowns (P = 0·096), shortage of surgical masks (P < 0·001), satisfaction to hospital's measures (P < 0·001), available guideline (P = 0·019), episodes with asymptomatic patients in surgical settings (P = 0·001), experiencing in-hospital infections (P = 0·002), and staff infections (P = 0·006). The multivariate analysis of these parameters revealed that shortage of surgical masks (OR: 1·605, 95%CI: 1·120-2·299, P = 0·01), unsatisfaction towards hospital's preventive measures (OR: 2·155, 95%CI: 1·650-2·813, P < 0·001) and experiencing in-hospital infections (OR: 1·457, 95%CI: 1·052-2·018, P = 0·024) were independently associated with surgeon's fear of getting infected. It is noteworthy that high caseload (>10 cases) of COVID-19 in the centers (P = 0·544 in univariate analysis) and countries' pandemic status of high risk (P = 0·729 in multivariate analysis) were not related to surgeon's fear. (High risk countries are defined as the ones with death case number of COVID-19 being more than 5000 on 8th April.)
Keywords: COVID-19; surgery